Dynamic Programming in a Generalized Courier Problem with Inner Tasks: Elements of a Parallel Structure - A. M. Grigoriev; E. E. Ivanko; A. G. Chentsov (Моделирование и анализ информационных систем)
In the article we concern the questions connected with the realization of a dynamic programming method in problems of consequent visiting of megapolises. The realization is complicated by precedence conditions and works inside the megapolises. The scheme for constructing a reduced (partial) array of Bellman function values using parallel computing without loss in accuracy is suggested. This procedure is realized on a multiprocessor computing system; parallelizing is performed at the stage of Bellman function layers construction.